2016
DOI: 10.1016/j.ijpharm.2016.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-loaded liposomes: The effect of lipid composition and purification on drug encapsulation and in vitro toxicity

Abstract: to an improvement in the loading capacities of DOPC-based liposomes only. Up to 3.6-fold 11 decrease in drug loading was observed after liposome purification, likely due to the loss of 12 adsorbed and loosely entrapped DTX in the SEC column. Our in vitro toxicity results in PC3 13 monolayer showed that non-purified, DTX-loaded DOPC:Chol liposomes were initially (24 h) 14 more potent than the purified ones, due to the fast action of the surface-adsorbed drug. 15However, we hypothesize that over time (48 and 72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…The results of weight monitoring indicated no significant loss of mouse body weight over time. Since body weight loss could be used as a sign of toxicity 52 , these results confirm that there is an relatively safe profile in the mice at the test dose for in vivo administration ( Fig. 4A upper and lower).…”
Section: Resultssupporting
confidence: 69%
“…The results of weight monitoring indicated no significant loss of mouse body weight over time. Since body weight loss could be used as a sign of toxicity 52 , these results confirm that there is an relatively safe profile in the mice at the test dose for in vivo administration ( Fig. 4A upper and lower).…”
Section: Resultssupporting
confidence: 69%
“…[51] Several liposomal characteristics are important for DTX delivery and the composition plays a central role, which is demonstrated in several reports in the literature. [52][53][54][55] For instance, Pereira et al [56] evaluated the effect of different lipids, DOPC, DPPC, and DSPC, on both the purification of DTX-loaded liposomes and cytotoxicity on prostate cancer (PC3) spheroids. The results showed that the use of DOPC, the only unsaturated lipid, caused higher loading compared to more rigid liposomes, prepared with the saturated lipids DPPC and DSPC.…”
Section: Introductionmentioning
confidence: 99%
“…This may be caused by interactions between hydrophobic tails of DSPE-PEG and phospholipids occupying potential drug-loading areas. 35,44 The encapsulation rates were sufficient to deliver equivalents of 40 and 80 µg/mL of DTX into PC-3 cell cultures. Liposome stocks were diluted in PBS to obtain 400 µg/mL of DTX, followed by a subsequent 1:10 or 1:5 dilution into RPMI medium to achieve final concentrations of 40 and 80 µg/mL, respectively.…”
Section: -41mentioning
confidence: 99%
“…34,35 Freshly prepared DTX-loaded liposomes or polypeptide/liposome nanoparticles were diluted into release buffer at a final polypeptide concentration of 25 µM and a liposome to polypeptide ratio of 1:10 (v/v). Final volumes of 550 µL were placed into a rinsed dialysis tubing cellulose membrane with 1.4 kDa molecular weight cutoff.…”
Section: Release Rate Analysismentioning
confidence: 99%